Interaction of Your Picture Learning Model Picture of Science Learning In Elementary School - Anita Rahayu; Dina Rahmawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
Education is a continuous (eternal) process of higher adjustment for human beings has developed physically and mentally, free and conscious of God, as manifested in the intellectual, emotional and human environment of humans. Learning is a process characterized by self change. The objectives to be achieved in this learning improvement process are: using the picture and picture learning method can improve student learning outcomes in the eyes science lessons. For this reason, researchers want to do this research as an increase in student learning outcomes using the Picture And Picture-based learning model. This study involved 15 people in class IV SD Negeri 002 Kabun. This study uses research consisting of introduction, planning, action, observation and reflection (evaluation). The results of the study found that students' learning mastery increased from cycle I to cycle II as much as 100% is declared complete. For this reason, teachers can use the model Picture and Picture-based learning in improving student learning outcomes in Science subjects Natural Knowledge (IPA).